Taking Severe Acute Malnutrition Treatment Back to the Community: Practical Experiences from Nutrition Coverage Surveys - Blanárová, Lenka; Rogers, Eleanor; Magen, Carine; Woodhead, Sophie (Frontiers in Public Health, 2016)
The Community Management of Acute Malnutrition (CMAM) treatment model was introduced to respond to the limited coverage of the inpatient model yet until the introduction of quick and low-cost approaches to measuring coverage, its reach was unknown. Once the Coverage Monitoring Network had been created to introduce the routine measurement of direct coverage estimates to implementers, they found that programmes were reaching only a third of cases. The barriers found to be limiting coverage were the result of the limited perceived value, and therefore focus, on the community. Therefore the network used the coverage assessment methodology as a way to encourage implementers to engage more fully with the community. By introducing small changes to the project cycle, specifically a participatory approach to assessments, programme design and implementation, the Coverage Monitoring Network have changed the way implementers’ engage with the community. Instead of viewing them as passive receivers of services, they have shifted their perspective to view them as service delivery partners. The process provides implementers with a deeper understanding of the context, while allowing the community to better understand the programme, its challenges and the identification of solutions. The Network observed implementers from ministries of health and non-governmental organisations adjusted their understanding and approach to service provision which is critical if we are to see sustainable increases in programme coverage. These experiences show that there is an appetite from implementers in multiple contexts for these practical and simple tools for re-engaging the community.